The Characteristic and The Use of Pelung Chicken in Indonesia - Iskandar, Sofjan; Susanti, Triana (Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Pelung chicken is one of livestock genetic resources in Indonesia, which has been playing an important role for years in the villagers in West Java Province. Pelung chicken originally came from Cianjur district in West Java area. It has been raised as a singing cockerel. This singing ability of the cockerel has become the main criteria for Pelung chicken regular competition in Cianjur. A serious attention on Pelung chicken can maintain the existence of Pelung chicken. The specific character of Pelung chicken compared to other native chicken in Indonesia is the large size of its body. This character could be used to improve the growth rate up to 20% bodyweight and the feed utilization efficiency up to 10% when crossbred with Kampung chicken. The economic value of Pelung chicken is not only its beautiful voice but also as a source of local chicken meat. Further research on any genetic potential of Pelung chicken is strongly suggested. Â  Key words: Pelung chicken, characteristic, the use of